2013
DOI: 10.1186/1756-3305-6-73
|View full text |Cite
|
Sign up to set email alerts
|

A shift from Indoor Residual Spraying (IRS) with bendiocarb to Long-Lasting Insecticidal (mosquito) Nets (LLINs) associated with changes in malaria transmission indicators in pyrethroid resistance areas in Benin

Abstract: BackgroundIndoor residual spraying (IRS) was implemented in the department of Ouémé-Plateau, southern Benin, in 2008 and withdrawn in 2011, when long lasting insecticidal nets (LLINs) were distributed to the communities that were previously targeted by IRS. Did the LLIN strategy provide a better level of protection against malaria transmission than IRS?MethodsEntomological surveillance was carried out to assess indicators of transmission risk during the last year of IRS and the first year after the LLIN interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Either data are unavailable or no previous attempts were made about the impact of IRS on SR in Ethiopia. However, studies from other African countries [27,28] demonstrated that the implementation of IRS reduced SR to non-detectable level, which is consistent with the results of the present study. And these would substantiate the contribution of IRS implementation in reducing malaria transmission risks in general and SR in particular in the present study area and others having similar ecological setups.…”
Section: Discussionsupporting
confidence: 93%
“…Either data are unavailable or no previous attempts were made about the impact of IRS on SR in Ethiopia. However, studies from other African countries [27,28] demonstrated that the implementation of IRS reduced SR to non-detectable level, which is consistent with the results of the present study. And these would substantiate the contribution of IRS implementation in reducing malaria transmission risks in general and SR in particular in the present study area and others having similar ecological setups.…”
Section: Discussionsupporting
confidence: 93%
“…Olayemi & Ande [31] had earlier correlated rainfall with mean monthly mosquito abundance in Kwara State. Osse et al [32] also reported higher human biting rate in second year compared to the first as a result of higher rainfall in some communities under IRS in Benin. However, the impact of DL installation in the intervention community was evident as significant ( P = 0.005) increase in rainfall did not translate to significant ( P = 0.067) increase in Anopheles densities from first to second year.…”
Section: Discussionmentioning
confidence: 99%
“…The main malaria vector control tools are indoor residual spraying (IRS), and long-lasting insecticide-impregnated bednets. The correct use of these tools depends on mosquito biting and resting behaviour, as well as their susceptibility to the applied insecticides (7). Extensive and long-term use of chemicals in malaria vector control programmes leads to changes in vector behaviour (8).…”
Section: Introductionmentioning
confidence: 99%